1999
DOI: 10.1046/j.1365-2265.1999.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of the metabolic syndrome in young women with the polycystic ovary syndrome and the effect of long‐term oestrogen–progestagen treatment

Abstract: These data indicate that hyperinsulinaemia and insulin resistance tended to worsen spontaneously in women with PCOS, without any worsening of the hyperandrogenism. Long-term oestrogen-progestagen treatment countered this tendency, probably because it improved the pattern of body fat distribution, by reducing abdominal fat depots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 45 publications
9
73
0
2
Order By: Relevance
“…However, regardless of alterations of insulin secretion, in a 10 y follow-up study we found that both fasting and glucose-stimulated insulin and C-peptide tended to further significantly increase in PCOS women, suggesting a worsened insulin resistant state with time. 77 In the same study we also found that several women developed impaired glucose tolerance. Longitudinal data are therefore warranted to investigate which factor, namely progressive insulin resistance and=or subtle alterations of insulin secretion, may predict the well-documented susceptibility of obese PCOS women toward type 2 diabetes.…”
Section: Androgen Abnormalitiessupporting
confidence: 59%
See 1 more Smart Citation
“…However, regardless of alterations of insulin secretion, in a 10 y follow-up study we found that both fasting and glucose-stimulated insulin and C-peptide tended to further significantly increase in PCOS women, suggesting a worsened insulin resistant state with time. 77 In the same study we also found that several women developed impaired glucose tolerance. Longitudinal data are therefore warranted to investigate which factor, namely progressive insulin resistance and=or subtle alterations of insulin secretion, may predict the well-documented susceptibility of obese PCOS women toward type 2 diabetes.…”
Section: Androgen Abnormalitiessupporting
confidence: 59%
“…114 In addition, by investigating the long-term effect of oral contraceptive therapy on metabolism and body composition in a group of PCOS women we found a significant reduction of waist circumference and of WHR, as well as of basal insulin levels and an improvement of glucose tolerance in some subjects. 77 These favorable effects were not, however, observed in a group of non-treated women, who had worsened fasting and glucose-stimulated insulin levels. Although controversy still exists concerning the effect of oral contraceptive preparations on glucose metabolism and insulin secretion and action in non-PCOS women, the results of this study indicate a potential benefit of long-term estroprogestagen compounds in body composition and the glucose-insulin system at least in PCOS women.…”
Section: Other Drugsmentioning
confidence: 90%
“…IR constitutes a prerequisite for diabetes mellitus (DM) and/or metabolic syndrome development, and consequently the increased incidence of these two morbidities in women with PCOS, compared with their BMI-matched peers, is expected (5,6,7,8,9). However, the available prospective studies reporting the significantly higher incidence of DM in women with PCOS compared with general population are few and DM is found mainly in obese women with the syndrome (10,11,12).…”
Section: Introductionmentioning
confidence: 87%
“…Plasma glucose levels were determined by the glucose oxidase technique immediately after blood was drawn. Levels for insulin, total testosterone, DHEA and its sulfate (DHEA-S), androstenedione, 17-OHP, SHBG, and cortisol were determined as previously described (18,27,28). The intra-assay coefficients of variation in our laboratory were 3.0% for insulin, 7.0% for total testosterone, 9.0% for DHEA, 5.9% for DHEA-S, 6.0% for androstenedione, 13.0% for 17-OHP, 6.5% for SHBG, and Ͻ8.0% for cortisol.…”
mentioning
confidence: 99%